(untitled) (International Association of Biologicals and Computational Digest, 2023)
This study explores the vital role of wild edible plants in the diets of indigenous communities in Mandvi Taluka, Surat district. Selecting eight villages based on their proximity to the forest, the research uncovers the nuanced relationships between geographic location and traditional plant use. These plants, integral to daily meals, offer essential nutrition and contribute to the local health system. Additionally, they play a crucial role in addressing hunger and food security challenges. The findings emphasize the need to preserve and promote these wild edibles for their cultural significance and potential contributions to a resilient local food system.